Diagnostic accuracy of Bilateral Inferior Petrosal Sinus Sampling: The Experience of a Tertiary Centre - Pereira, Catarina A.; Ferreira, Lia; Amaral, Cláudia; Alves, Viriato; Xavier, João; Ribeiro, Isabel; Cardoso, Helena (Experimental and Clinical Endocrinology & Diabetes, 2019)
Purpose To assess the accuracy of bilateral inferior petrosal sinus sampling both in the differential diagnosis of adrenocorticotrophic hormone dependent Cushing’s syndrome and predicting the localization on the pituitary.Methods The authors evaluated all patients that undergone bilateral inferior petrosal sinus sampling in a tertiary centre, between January 1995 and March 2018. The probable diagnosis of Cushing’s disease was made when the basal central/peripheral gradient was>2 and/or>3 after stimulation with corticotrophin releasing hormone. The localization was suggested when the inter-sinus gradient was>1.4. The results obtained were compared with the post operatory results: compatible histology and positive immunohistochemistry to adrenocorticotrophic hormone and/or the presence of criteria of cure. Sensitivity, specificity and predictive positive value were calculated.Results A total of 49 patients were evaluated (75.5% female; mean age 45.4±16.3 years old). Bilateral inferior petrosal sinus sampling was compatible with Cushing’s disease in 27 out of 28 confirmed cases in histology or by criteria of cure, and was compatible with ectopic secretion in the 2 cases confirmed as ectopic secretion of adrenocorticotrophic hormone (sensitivity 96.4%; specificity 100%). The lateralization calculated was concordant with the results after surgery in 17 out of 27 patients with Cushing’s disease – predictive positive value of 63%. Magnetic resonance had a higher predictive value to lateralization – 70.0%.Conclusions Bilateral inferior petrosal sinus sampling is a safe and reliable procedure to diagnose Cushing’s disease, with great sensitivity and specificity. Nevertheless, the capacity of this procedure to lateralize the lesion inside the pituitary is limited.
Keywords: pituitary; Cushing’s syndrome; ACTH.